Peran Persepsi Pengembangan Karir, Kedisiplinan Kerja dan Kepemimpinan Terhadap Kinerja - Yessica Novianti; Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to determine the role of career development, work discipline, and leadership on employee performance. This research method uses quantitative descriptive research. This quantitative descriptive research aims to explain various conditions, various situations or various variables that arise. The sample of this study was taken from 79 employee respondents in one of the interior contracting companies in West Jakarta. Data analysis techniques used in this study are statistical hypotheses and testing, which consist of validity, reliability, classic assumption tests (normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test), and hypothesis testing methods (T test, F test, determination coefficient analysis (R2), correlation coefficient analysis (R)). The results are: (a) There is a positive role in career development in employee performance; (b) There is a positive role for work discipline in the performance of customer employees; (c) There is a positive role of leadership in employee performance; (d) The role of career development, work discipline, and leadership has a positive influence on employee performance, which can be concluded that if the three variables increase, employee performance is also positive or increased.